Factors Influencing Children's Tooth Brushing Intention: An Application of the Theory of Planned Behaviour. (9th August 2019) - Davison, Jenny; McLaughlin, Marian; Giles, Melanie
Objective: The aim of the present study was to employ the theory of planned behaviour (TPB) to predict and explain intentions and motivations to brush teeth among primary school children in Northern Ireland (NI). Design: Primary schools in NI were sorted by a number of key stratification variables and then randomly sampled. Twenty-seven schools took part in the research, and a questionnaire that incorporated both direct and indirect constructs of the TPB, related to tooth brushing behaviour, was administered to a sample of 867 year six school children. Results: Multiple regression analyses provided support for the TPB; together the TPB constructs predicted 57.1% of the variance in intentions to brush teeth. Correlational analyses confirmed self-efficacy as having the strongest association with intentions, followed by attitude, subjective norm and perceived control. Conclusion: The findings obtained in the present study suggest that the TPB is a useful framework for investigating children's tooth brushing intentions, and provides the foundation for designing an intervention aimed at encouraging tooth brushing behaviour among children.